The Impact of Technological Advances and the Pandemic on Changes in Consumer Consumption Behavior in Modern Retail in Indonesia - Suriansha, Reza (The Eastasouth Management and Business, 2025)
In recent years, consumer behavior in Indonesia has experienced significant transformations, driven primarily by technological advancements and the global pandemic. These shifts have profoundly impacted business strategies and operational models across various industries in Indonesia. Retailers are forced to adapt to digital trends by leveraging technology to enhance customer experiences and optimize their online presence. This study employs a quantitative approach to examine these dynamics. The findings reveal that technological advancements and the pandemic significantly influence consumer behavior, particularly due to the rapid growth of modern retail markets and the increasing availability of shopping venues. While online shopping has become more prevalent, this does not necessarily indicate a rise in overall consumerism. Consumption patterns remain shaped by various factors, including the economic climate, essential needs, and heightened awareness of financial management.